Academic performance and mental health among Chinese middle and high school students after the lifting of COVID-19 restrictions - Song, Hong-Jun; Mu, Yun-Fei; Wang, Cong; Cai, Jia; Deng, Zhong-Yue; Deng, Ai-Ping; Huang, Xue-Hua; Meng, Xian-Dong; Zhang, Lan; Huang, Yi; Zhang, Wei; Shen, Wen-Wu; et al. (Frontiers in Psychiatry, 2023)
Background: Although the COVID-19 pandemic has greatly changed the way students studied, it is still unknown about the impact of the COVID-19 pandemic on students' academic performance and mental health.Objective: To explore the academic performance and mental health status of middle and high school students after the lifting of COVID-19 restrictions in China.Methods: An online survey was conducted in Sichuan province, China from Dec 14, 2022 to Feb 28, 2023. All participants were students in middle and high schools, recruited via their teachers. The general information, COVID-19-related information, and academic performance were collected. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Internet Addiction Test (IAT) were used to assess the mental health problems.Results: Of 60268 participants, 36247 (60.2%) middle and high school students reported that their studies were affected by the COVID-19 pandemic, and 24864 (41.2%) reported that their academic performance had worsened. The prevalence of depression and anxiety symptoms was 38.4% and 32.7%, respectively. There was a significant association between academic performance change and mental health problems. The logistic regression analysis showed that improved academic performance was a protective factor for depression, and declined academic performance was a risk factor for depression and anxiety. Being COVID-19 infected, family members being infected, with quarantine experience, and with COVID-19-related stigma were risk factors for depression and anxiety.Academic studies and mental health status of middle and high school students in Sichuan, China have been negatively impacted by the COVID-19 pandemic, even after the lifting of COVID-19 restrictions. Students' academic performance, academic concerns, and mental health status should be considered for educational policymakers and institutions to improve students' academic studies and mental wellbeing.